(untitled) (TEST Ticontre. Theory Text Translation, 2023)
For many years, Fabrizio Cambi (1952-2021), a major figure in the Faculty of Humanities at the University of Trento, worked on the translation of the History of Agathon by Christoph Martin Wieland (1766/67), a key text of the German Enlightenment and a forerunner of the Bildungsroman. In his last months he came to complete it, but his early death prevented him from carrying out the last revision. This paper tries to recount him at work, by recalling conversations, emails, as well as the introduction and commentary to the novel written in preparation for its publication and still unpublished. The Agathon workshop thus yields the portrait of a man and an intellectual, who on the threshold of the new millennium looks to the past of German literature to imagine the future of the new generations, aware of the ethical and political implications of his work, in a never-ending yearning for utopia. Per molti anni Fabrizio Cambi (1952-2021), figura fondamentale della Facoltà di Lettere dell’Università di Trento, lavorò alla traduzione della Storia di Agatone di Christoph Martin Wieland (1766/67), testo chiave dell’illuminismo tedesco e anticipatore del Bildungsroman. Nei suoi ultimi mesi arrivò a completarla, ma la morte precoce gli impedì di compiere l’ultima, indispensabile revisione. Questo saggio cerca di raccontarlo al lavoro, ripercorrendo conversazioni, email, nonché l’introduzione e il commento al romanzo scritti in vista della sua pubblicazione e tuttora inediti. Dal laboratorio critico e traduttivo dell’Agathon esce così il ritratto di un uomo e di un intellettuale che alle soglie del nuovo millennio guarda al passato della letteratura tedesca per immaginare il futuro delle nuove generazioni, consapevole delle implicazioni etiche e politiche del proprio lavoro, in un mai sopito anelito verso l’utopia.